2017
DOI: 10.1007/s11239-017-1526-9
|View full text |Cite|
|
Sign up to set email alerts
|

Obstetric antiphospholipid syndrome and long term arterial thrombosis risk

Abstract: Antiphospholipid syndrome (APS) is classified as the association of a thrombotic event and/or obstetric morbidity in patients persistently positive for antiphospholipid antibodies and/or lupus anticoagulant. To evaluate the incidence of subsequent thrombosis among women diagnosed with purely obstetric APS. We retrospectively reviewed and collected demographic and clinical data from the computerized charts of all patients with obstetric APS, from 1992 to 2017. Eligibility criteria included all women diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…Case-tailored management was found probably because patients with less thrombotic events observed came from these specialized centers. We only found 31 cases (3.1%) in which thrombotic phenomena occurred, in contrast to what was published by Drozidnsky et al, where the thrombosis rate reached 12% [31]. In any case and contrary to what was classically thought, it seems that venous and/or arterial thromboses are not frequent complications among the OAPS patients.…”
Section: Tablecontrasting
confidence: 88%
“…Case-tailored management was found probably because patients with less thrombotic events observed came from these specialized centers. We only found 31 cases (3.1%) in which thrombotic phenomena occurred, in contrast to what was published by Drozidnsky et al, where the thrombosis rate reached 12% [31]. In any case and contrary to what was classically thought, it seems that venous and/or arterial thromboses are not frequent complications among the OAPS patients.…”
Section: Tablecontrasting
confidence: 88%
“…This idea is supported by two types of in vitro evidence, 12,13,33,34 and epidemiological observation that is uncommon for thrombotic manifestations to be present in patients with pregnancy morbidity. 10,35 These findings suggest that gestational manifestations cannot be explained by placenta infarction, as previously proposed, 36 and instead it can be described as a complement-dependent inflammatory injury. 37,38 Vascular APS and obstetric APS do not seemingly share pathological mechanisms and, thus, the syndrome manifests itself in two different ways (►Table 1).…”
supporting
confidence: 63%
“…108 Other authors have also reported an increased risk for long-term thrombosis after obstetric APS, 109 specially arterial cerebral events. 110 Nonetheless, most of publications could not identify clinical or laboratorial features that would indicate patients more likely to develop thrombosis. 110…”
Section: Thrombosis After Obstetric Aps (Summary Prepared By Dr Guilmentioning
confidence: 99%
“…110 Nonetheless, most of publications could not identify clinical or laboratorial features that would indicate patients more likely to develop thrombosis. 110…”
Section: Thrombosis After Obstetric Aps (Summary Prepared By Dr Guilmentioning
confidence: 99%